Noncooperative vs. minimum-rate commodity taxation - Morten Hvidt; Søren Bo Nielsen (Copenhagen Business School (CBS), Department of Economics, 2000)
This paper demonstrates, within a simple two-country model of commodity taxation and cross-border shopping, that the tax revenue (welfare) effects of a minimum tax requirement depend crucially on the character of the initial noncooperative tax equilibrium, i.e. whether it is Nash or Stackelberg.
hdl:10398/7644
Keywords: F15; H87; 330; Commodity tax; Minimum rate